Development and Freedom in Bangladesh Through the Lens of Amartya Sen’s “Development as Freedom” Pradigm (Philosophy and Progress, 2025)
This study investigates wh ther Bangladesh has been successful in transferring its social and economic development accomplishments to political development during the Awami League regime (2009–2023). The two main facets of development—economic and social—are, frequently, the only ones taken into account by modern techniques of evaluation. The other part of development, the political one, is frequently ignored by evaluation techniques. The majority of Bangladesh’s social and economic accomplishments are true, according to this study’s analysis of development as freedom, but they have not yet been applied to the country’s political arena. By comparing Bangladesh’s accomplishments to India’s through the lens of Amartya Sen’s concept of “Development as Freedom,” it is concluded that these successes have given Bangladesh “an uncertain glory.”Bangladesh’s achievements are primarily flawed by a lack of political freedom, in contrast to India’s achievements, which were marred by disparities and a slow pace of social growth.Philosophy and Progress, Vol#75-76; No#1-2; Jan-Dec 2024 P 31-84